Exploring the interaction of avian frugivory and plant spatial heterogeneity and its effect on seed dispersal kernels using a simulation model. Issue 9 (13th October 2016) - Pegman, Andrew P. McKenzie; Perry, George L. W.; Clout, Mick N.
Abstract : Seed dispersal by avian frugivores is one of the key processes influencing plant spatial patterns, but may fail if there is disruption of plant–frugivore mutualisms, such as decline in abundance of dispersers, fragmentation of habitat, or isolation of individual trees. We used simulation model experiments to examine the interaction between frugivore density and behaviour and the spatial arrangement of fruiting plants and its effect on seed dispersal kernels. We focussed on two New Zealand canopy tree species that produce large fruits and are dispersed predominantly by one avian frugivore ( Hemiphaga novaeseelandiae ). Although the mean seed dispersal distance decreased when trees became more aggregated, there were more frugivore flights between tree clusters, consequently stretching the tails of the dispersal kernels. Conversely, when trees were less aggregated in the landscape, mean dispersal distances increased because seeds were deposited over larger areas, but the kernels had shorter tails. While there were no statistically meaningful changes in kernel parameters when frugivore density changed, decreases in density did cause a proportional reduction in the total number of dispersed seeds. However, birds were forced to move further when fruit availability and fruit ripening were low. Sensitivity analysis showed that dispersal kernels were primarily influenced by the model parameters relating to disperser behaviour, especially those determining attractiveness based on distance to candidate fruiting trees. Our results suggest that the spatial arrangement of plants plays an important role in seed dispersal processes – although tree aggregation curbed the mean seed dispersal distance, it was accompanied by occasional long distance events, and tree dispersion caused an increase in mean dispersal distance, both potentially increasing the probability of seeds finding suitable habitats for germination and growth. Even though low frugivore densities did not cause dispersal failure, there were negative effects on the quantity of seed dispersal because fewer seeds were dispersed.